In vivo study of a locally manufactured hydroxyapatite-based material as bone replacement material - Razak, Noor Hayati Abdul; Samsudin, Ab. Rani; Omar, Nor Shamsuria (Pusat Pengajian Sains Pergigian Universiti Sains Malaysia, 2004)
The objective of the study is to evaluate the osteoconductive, osteoinductive and biocompatibility properties of a locally produced dense hydroxyapatite (HA) as bone replacement material in mandibles. The study was carried out on 8 New Zealand White rabbits. Defects were created in the mandible of a rabbit model whereby the right side was implanted with HA while the left side was left empty to act as a control. The dense HA blocks with the pore size of < 5J.1m promotes bone ingrowth as early as 4 weeks when viewed by the topographic method. Both the implant and control sites were evaluated clinically and histologically at 4, 12, 20, 22 weeks interval. Enhancement of osteoconduction was evident by the presence of abundant capillaries, perivascular tissue and osteoprogenitor cells of the host accounting for the new bone filling the gap and remodelling taking place. This study demonstrated that the dense HA exhibits excellent biocompatibility as noted by the complete absence of reactive cells. HA also promotes osteoconduction. It appears that this locally manufactured HA has the potential to be a valuable replacement material for maxillofacial reconstructive surgery and orthopaedic surgery.